Neurosyphilis Presenting as Asymptomatic Optic Perineuritis. (26th February 2012) - Parker, Sarah E.; Pula, John H.
Abstract : Introduction . Syphilis is a sexually transmitted disease that is known as "the great imitator" due to its wide variety of clinical presentations, including ocular disorders. There has been an increase in the rate of syphilis in the United States, especially in persons with HIV. We report a case of optic perineuritis in an asymptomatic male secondary to central nervous system (CNS) syphilis. Case Report . A 41-year-old man was found to have bilateral disc edema on a routine exam. Brain MRI was unremarkable, and lumbar puncture revealed a normal opening pressure, with an elevated cerebrospinal fluid white cell count. Orbit MRI showed optic nerve sheath expansion and enhancement, consistent with optic perineuritis. He tested positive for syphilis based on serum RPR and FTA-ABS. Conclusion . Ophthalmologic findings, including disc edema, may be the presenting features of CNS syphilis. Even in asymptomatic persons, perineuritis should be considered early, as diagnosis and treatment are imperative given the progressive nature of the disease.